PENERAPAN PENDEKATAN KOMUNIKATIF UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS VA SDN 003 BINA BARU KAMPAR KIRI TENGAH - Perwitasari, Siti; Kurniaman, Otang; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Problems in this study are students who feel embarrassed and afraid to speak, especially speaking in front of the class. A research is improve student’s speaking skills. In improving student’s speaking skills the researcher applies a communicative approach using classroom action research methods. This research was conducted 2 cycles consisting of planning, action implementation, observation and reflection. Based on the results of Indonesian language learning research with the application of communicative approach shows an increase in speaking skills of class VA SDN 003 Bina Baru Kampar Kiri Tengah student’s both orally and in writing. This increase can be seen from the observation and implementation of corrective actions in each cycle. Cycle I that get very skilled result there are 1 person (4.76%), skilled there are 6 people (28,57%), skilled enough 11 people (52,38%), less skilled there are 3 people (23,81% ) and no students are not yet skilled. In the second cycle that got highly skilled results there were 5 people (23.81%), skilled there were 12 people (57.14%), quite skilled there were 4 people (19.05%) and no less skilled and unskilled students skilled. The observation of teacher activity in cycle I and first cycle of first meeting 63.89% increased to 83.33%, at the second meeting 68.06% increased to 91.67%. The result of observation of student activity on cycle I and first cycle of 57,78% first meeting increased to 77,78%, at second meeting 66,57% increased to 83,34%. Thus it can be said that learning communicative approach can improve student’s speaking skill result.Keywords: Speaking Skills, Bahasa Indonesia, Communicative Approach